Design and fabrication of nutmeg grater - Shamsul Niza, Nur Izzah Putri; Mohd Yusof, Ab Aziz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
A nutmeg grater is essential for grinding nutmeg into a fine powder, but conventional designs pose risks of accidental cuts. To address this issue, a safer and more user-friendly nutmeg grater should be developed, ensuring ease of use for both adults and children. This innovation aims to reduce kitchen injuries while simplifying the cooking process. To gather relevant data, surveys will be distributed, and online research will be conducted to analyse existing designs and user concerns. The project focuses on designing and fabricating a scaled down, manually operated nutmeg grater with a simple hand crank mechanism, making it both practical and efficient for home kitchens. The methodologies for this project outlining as the design, material selection, and fabrication process. The expected outcome is a fully functional and safe nutmeg grater capable of efficiently grating nutmeg, fruits, and soft vegetables, ultimately enhancing kitchen safety and usability.